Estimation of the concrete frames by means of environmental safety indicators - Хімічева, Ганна Іванівна; Молибог, Віталій Вікторович; Колесіна, Наталія Василівна (Eastern-European Journal of Enterprise Technologies, 2012)
The questions of ecological safety are considered in a build industry. Negative influence is well-proven on the organism of man of build materials with enhanceable maintenance of harmful matters, the mechanisms of their determination and estimation are offered